The Barriers to a Healthy Lifestyle in Employed Mothers of Toddlers - Mansoureh Kashefi; Sima Mohammad Khan Kermanshahi; Mohammad Gholami Fesharaki (Journal of Holistic Nursing and Midwifery)
Introduction: Mothers form the core of the family unit. They also play an important role in the success and health of other family members. Hence, the health and development of any society is largely based on women s health. The health of working women with toddlers, which can be affected by changes in lifestyle, is the need of the modern society. Therefore, identifying barriers to a healthy lifestyle is essential to promote women s health. Objective: This study aimed to determine the barriers to a healthy lifestyle related to the health of working mothers with toddlers from the mother s perspective. Materials and Methods: This was an analytical cross-sectional study conducted on 60 working mothers with toddlers in Semnan City in 2015. For this purpose, all mothers with toddlers whose children attended kindergarten, were included in the study. After collecting and recording the mothers demographic data, the Lifestyle Standardized Questionnaire was administered to them to measure 10 aspects of physical health, sports and fitness, weight and nutrition management, disease prevention, psychological health, mental health, social health, avoiding drugs, prevention of disasters, and environmental health. Then, the researcher-made 34-item questionnaire of obstacles to lifestyle in three domains of physical health, psychological health, and social health was filled by the mothers. The data were analysed using descriptive statistics and the Chi-square test to determine the relationship between the variables. Results: About 70% of the mothers were 30 years or older. Regarding the physical aspect, there was a neglect of physical activity due to abundant work occupation (71.7%). Regarding the psychological health aspect, the working mother s fear and concern about her child s disease in kindergarten (61.7%) was paramount. In the social health aspect, the presence of work induced by familial life requirements (as a mother, wife) (65%) obtained the most scores as barriers to a healthy lifestyle. According to the Chi-square test, there was no meaningful relationship between the demographic variables and barriers to a healthy lifestyle (P=0.05). Conclusion: The results of this study could be a step towards identifying effective factors and then developing a strategy to promote a healthy lifestyle among working mothers with toddlers.